Types and sequences of self‐regulated reading of low‐achieving adolescents in relation to reading task achievement. (18th October 2014) - de Milliano, Ilona; van Gelderen, Amos; Sleegers, Peter
Abstract : This study examines the relationship between types and sequences of self‐regulated reading activities in task‐oriented reading with quality of task achievement of 51 low‐achieving adolescents (Grade 8). The study used think aloud combined with video observations to analyse the students' approach of a content‐area reading task in the stages of orientation, text reading and answering questions. Results show that in general these low‐achieving adolescents are infrequently monitoring their text comprehension or making connections with prior knowledge. Nevertheless, important differences are found between types and sequences of self‐regulated reading activities related to task achievement. The low‐achieving adolescents showing a straightforward linear approach to the task (orientation, reading of the whole text and finally answering of questions) yielded more success. In addition, readers demonstrating more activities directed at connections between text contents and prior knowledge during reading showed better task achievement. Implications of these findings for literacy education of this special group of adolescents are discussed.